Restraint Stress Intensifies Interstitial K+ Accumulation during Severe Hypoxia - Schnell, Christian; Janc, Oliwia; Kempkes, Belinda; Araya-Callis, Corolina; Flügge, Gabriele; Hülsmann, Swen; Müller, Michael (Frontiers in Pharmacology, 2012)
Chronic stress affects neuronal networks by inducing dendritic retraction, modifying neuronal excitability and plasticity, and modulating glial cells. To elucidate the functional consequences of chronic stress for the hippocampal network, we submitted adult rats to daily restraint stress for three weeks (6 h/day). In acute hippocampal tissue slices of stressed rats, basal synaptic function and short-term plasticity at Schaffer collateral/CA1 neuron synapses were unchanged while long-term potentiation was markedly impaired. The spatiotemporal propagation pattern of hypoxia-induced spreading depression episodes was indistinguishable among control and stress slices. However, the duration of the extracellular direct current (DC) potential shift was shortened after stress. Moreover, K+ fluxes early during hypoxia were more intense, and the postsynaptic recoveries of interstitial K+ levels and synaptic function were slower. Morphometric analysis of immunohistochemically stained sections suggested hippocampal shrinkage in stressed rats, and the number of cells that are immunoreactive for GFAP (glial fibrillary acidic protein) was increased in the CA1 subfield indicating activation of astrocytes. Western blots showed a marked downregulation of the inwardly rectifying K+ channel Kir4.1 in stressed rats. Yet, resting membrane potentials, input resistance and K+-induced inward currents in CA1 astrocytes were indistinguishable from controls. These data indicate an intensified interstitial K+ accumulation during hypoxia in the hippocampus of chronically stressed rats which seems to arise from a reduced interstitial volume fraction rather than impaired glial K+ buffering. One may speculate that chronic stress aggravates hypoxia-induced pathophysiological processes in the hippocampal network and that this has implications for the ischemic brain.